Does functional health status predict health-related quality of life in children after Fontan operation?. (23rd April 2015) - Dulfer, Karolijn; Bossers, Sjoerd S. M.; Utens, Elisabeth M. W. J.; Duppen, Nienke; Kuipers, Irene M.; Kapusta, Livia; van Iperen, Gabrielle; Schokking, Michiel; ten Harkel, Arend D. J.; Takken, Tim; Helbing, Willem A.
Abstract: Purpose: It is important to identify those children with a Fontan circulation who are at risk for impaired health-related quality of life. We aimed to determine the predictive value of functional health status – medical history and present medical status – on both physical and psychosocial domains of health-related quality of life, as reported by patients themselves and their parents. Methods: We carried out a prospective cross-sectional multi-centre study in Fontan patients aged between 8 and 15, who had undergone staged completion of total cavopulmonary connection according to a current technique before the age of 7 years. Functional health status was assessed as medical history – that is, age at Fontan, type of Fontan, ventricular dominance, and number of cardiac surgical procedures – and present medical status – assessed with magnetic resonance imaging, exercise testing, and rhythm assessment. Health-related quality of life was assessed with The TNO/AZL Child Questionnaire Child Form and Parent Form. Results: In multivariate prediction models, several medical history variables, such as more operations post-Fontan completion, lower age at Fontan completion, and dominant right ventricle, and present medical status variables, such as smaller end-diastolic volume, a higher score for ventilatory efficiency, and the presence of sinus node dysfunction, predicted worse outcomes on several parent-reported and self-reported physical as well as psychosocial health-related quality of life domains. Conclusions: Medical history and worse present medical status not only predicted worse physical parent-reported and self-reported health-related quality of life but also worse psychosocial health-related quality of life and subjective cognitive functioning. These findings will help in identifying patients who are at risk for developing impaired health-related quality of life.